2020
DOI: 10.3390/en13061466
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Use of Electric Drive Systems for Crew Transfer Vessels Servicing Offshore Wind Farms

Abstract: The article presents issues related to the possibility of using electric propulsion systems in units used to transport crews servicing wind towers at sea. Offshore wind energy issues are discussed. Proposals for electric propulsion systems that could be used on units for transporting crews servicing offshore wind farms are presented. The possibility of using purely electrical drive systems or hybrid drive systems operating in a diesel-electric configuration is analyzed. By observing the motion of real CTV unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…In the present study, the strongest vibrations were observed for the cylinder of the largest diameter starting from α = 4.8. The presented study described the method of reliable experimental prediction of the hydrodynamic force as a first part of further studies on the active control of rotor-generated flow [ 22 ] and bow steering system for river barges and vessels with expected good maneuverability, operated under current, wind, and waves [ 23 ]. The novelty of the paper is the investigation on the possibility of modeling the rotor-generated hydrodynamic force for the low aspect cylinders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the strongest vibrations were observed for the cylinder of the largest diameter starting from α = 4.8. The presented study described the method of reliable experimental prediction of the hydrodynamic force as a first part of further studies on the active control of rotor-generated flow [ 22 ] and bow steering system for river barges and vessels with expected good maneuverability, operated under current, wind, and waves [ 23 ]. The novelty of the paper is the investigation on the possibility of modeling the rotor-generated hydrodynamic force for the low aspect cylinders.…”
Section: Discussionmentioning
confidence: 99%
“…The presented study described the method of reliable experimental prediction of the hydrodynamic force as a first part of further studies on the active control of rotor-generated flow [ 22 ] and bow steering system for river barges and vessels with expected good maneuverability, operated under current, wind, and waves [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 for Robust controller in 700 [s]. Multidimensional controllers can also be used in small ships used in autonomous transport systems in coastal and inshore waters [ 48 , 49 , 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore electric drives are also used in vessels' drive systems. An example of a vessel servicing crew transfer from off-shore wind farms is analyzed in [4], as using electric drives in vessels leads to a significant reduction in fuel consumption. It seems that the development of two and multilevel three-phase converters is continually maintained, particularly in the application domain [5].…”
Section: Introductionmentioning
confidence: 99%